Reduction of von Willebrand Factor by Endothelial Cells - Xie, Lijuan; Chesterman, Colin N.; Hogg, Philip J. (Thrombosis and Haemostasis, 2000)
The haemostatic activity of plasma von Willebrand factor (vWF) is a function of multimer size. Only the large vWF multimers are effective in promoting platelet adhesion to a site of vascular injury. We observed that the conditioned medium of cultured human umbilical vein, human microvascular and bovine aortic endothelial cells contained an activity which reduced the average multimer size of plasma or purified vWF. The average multimer size of vWF produced endogenously by human umbilical vein endothelial cells was similarly reduced following secretion. The reducing activity was ablated by pre-treatment with heat or the thiol blocking agents, iodoacetamide, N-ethylmaleimide or E-64, but not by a range of specific serine-, cysteine-, aspartic-, or metalloproteinase inhibitors. Reduction in vWF multimer size was associated with formation of new thiols in vWF and there was no evidence for additional proteolytic processing of vWF. The reducing activity was associated with a protein with an anionic pI that binds heparin and contains reactive thiol(s). These results suggested that the interchain disulfide bonds that link the vWF homodimers near the N-termini were being reduced by a vWF reductase secreted by endothelial cells. In support of this hypothesis, incubation of vWF with the protein reductants, protein disulfide isomerase and thioredoxin, resulted in formation of new thiols in vWF and reduction in the average multimer size of vWF. These findings may have consequences for control of vWF haemostatic activity.Abbreviations: BAEC, bovine aortic endothelial cell; BSA, bovine serum albumin; cm, conditioned medium; GSH, reduced glutathione; HUVEC, human umbilical vein endothelial cell; HDMVEC, human dermal microvascular endothelial cell; IAM, iodoacetamide; MPB, 3-(N-maleimidylpropionyl)biocytin; NEM, N-ethylmaleimide; PDI, protein disulfide isomerase; PVDF, polyvinylidene difluoride; vWF, von Willebrand factor.
Keywords: von Willebrand factor; endothelial cell; reductase